The Effect of Investment on Economic Growth in North Sumatra in 2007-2021 - Haddad Alwi (Outline Publisher, 2023)
This study aims to determine the effect of investment on economic growth in North Sumatra. This research is based on quantitative data types and their data sources from secondary data. The analytical data in this study was taken from the Central Statistics Agency of North Sumatra from 2007-2021. The analysis method used in this study is multiple linear regression analysis. This analysis includes classical assumption testing, multiple regression analysis and hypothesis testing through t and F tests. The results of the F test show that investment variables have a significant effect on economic growth in North Sumatra.